HUBUNGAN ANTARA INDEKS DURABILITAS DENGAN DURABILITAS ASPAL - Madi Hermadi; M. Sjahdanulirwan (Jurnal Jalan-Jembatan, 2005)
Asphalt durability level has to be known early or before the asphalt is decided to be used for pavement. In principle, asphalt durability level can be known base on chemical composition. The asphalt that has more reactive component has lower durability level than the asphalt that has more unreactive component. To know asphalt durability level, the reactive component compare with the unreactive component and it is called durability index. On the other hand, SUPERPAVE has developed TFOT (Thin Film Oven Testing) and PAV (Pressure Agging Vessel) testing to simulate field condition of asphalt in pavement. By this test, asphalt durability can be predicted. This paper explains the relation of asphalt durability index base on asphalt chemical composition with asphalt durability base on TFOT and PAV testing. The results, there isn’t correlation between asphalt durability index with asphalt durability based on TOFT and PAV. Because of that, to predict durability of asphalt, it is better if use conditioning by TFOT and PAV as SHRP recommendation.